Origin of Extremely Intense Southward Component of Magnetic Field (Bs) in ICMEs - Shen, Chenglong; Chi, Yutian; Xu, Mengjiao; Wang, Yuming (Frontiers in Physics, 2021)
The intensity of the southern component of \modi{the} magnetic field ($B_s$) carried by Interplanetary Coronal Mass Ejections (ICMEs) is one of the most critical parameters in causing extreme space weather, such as intense geomagnetic storms. In this work, we investigate \modi{three} typical ICME events with extremely intense $B_s$ in detail and present a statistical analysis of origins of intense $B_s$ in distinct types of ICMEs based on the ICME catalogue from 1995 to 2020. According to the in-situ characteristics, the ICME events with extremely high $B_s$ are classified into \modi{three} types: \modi{isolated ICMEs},multiple ICMEs, \modi{shock-ICME interaction events with shocks inside ICMEs, or shocks passed through ICMEs.} By \modi{analyzing} all ICME events with $B_s \ge 10$nT and $B_s \ge 20$nT, \modi{we find} that the interaction events\modi{,} particularly the shock-ICME interaction events have a greater chance of carrying extreme intense $B_s$. \modi{Only based on the in-situ observations at Earth, some interacting ICME events, such as shock-ICME interaction events with shocks passed through the preceding ICME or ICME cannibalism, could be classified as isolated ICME events. This may lead to an overestimation of the probability of ICME carrying extremely intense $B_s$.} To further investigate such events, direct and \modi{multi-point} observations of \modi{the} CME propagation in the inner heliosphere from the Solar Ring Mission could be \modi{crucial}.